Dose-response relationship between ambulatory load magnitude and load-induced changes in COMP in young healthy adults. Issue 1 (January 2019) - Herger, S.; Vach, W.; Liphardt, A.-M.; Egloff, C.; Nüesch, C.; Mündermann, A.
Summary: Objective: To determine the dose-response relationship between ambulatory load magnitude during a walking stress test and load-induced changes in serum concentration of cartilage oligomeric matrix protein (sCOMP) in healthy subjects. Design: sCOMP was assessed before and after a 30-min walking stress test performed on three test days by 24 healthy volunteers. In each walking stress test, one of three ambulatory loads was applied in a block randomized crossover design: normal body weight (BW) (100%BW = normal load); reduced BW (80%BW = reduced load); increased BW (120%BW = increased load). Knee kinematics and ground reaction force (GRF) were measured using an inertial sensor gait analysis system and a pressure plate embedded in the treadmill. Results: Load-induced increases in sCOMP rose with increasing ambulatory load magnitude. Mean sCOMP levels increased immediately after the walking stress test by 26.8 ± 12.8%, 28.0 ± 13.3% and 37.3 ± 18.3% for the reduced, normal or increased load condition, respectively. Lower extremity kinematics did not differ between conditions. Conclusions: The results of this study provide important evidence of a dose-response relationship between ambulatory load magnitude and load-induced changes in sCOMP. Our data suggests that in normal weight persons sCOMP levels are more sensitive to increased than to reduced load. The experimental framework presented here may form the basis for studying the relevance of the dose-response relationship between ambulatory load magnitude and load-induced changes in biomarkers involved in metabolism of healthy articular cartilage and after injury.